2013
DOI: 10.1136/bmj.f2827
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the organisation of stroke services, process of care, and mortality in England: prospective cohort study

Abstract: Objective To estimate the relations between the organisation of stroke services, process measures of care quality, and 30 day mortality in patients admitted with acute ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
99
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 31 publications
5
99
0
6
Order By: Relevance
“…6 In the inpatient setting, there is strong evidence that patients managed on organized inpatient stroke units have much better clinical outcomes. 7 Stroke unit care reduces the likelihood of death and disability in men and women of any age with mild, moderate, or severe stroke by as much as 30%. 8 Additionally, rapid assessment and management of patients with TIA also has strong evidence to its effectiveness.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…6 In the inpatient setting, there is strong evidence that patients managed on organized inpatient stroke units have much better clinical outcomes. 7 Stroke unit care reduces the likelihood of death and disability in men and women of any age with mild, moderate, or severe stroke by as much as 30%. 8 Additionally, rapid assessment and management of patients with TIA also has strong evidence to its effectiveness.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Prehospital triage and transportation protocols should identify facilities locally or regionally designated to receive acute stroke patients and bypass more proximal facilities in favor of transporting to these sites, assuming the absence of other immediately life-threatening conditions (STRONG RECOMMENDATION, MODERATE QUALITY EVIDENCE). 5,7,10,11 2. Emergency departments that treat acute stroke patients should have "Code Stroke" protocols or stroke teams to rapidly assess, image and treat patients with the highest priority (STRONG RECOMMENDATION, MODERATE QUALITY EVIDENCE).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Antiplatelet drugs for ischemic stroke (IS) -Aspirin administration reported in two studies (25,43) was combined with a KPI for antiplatelet drugs for ischemic stroke reported in seven studies (17,18,21,23,24,28,40).…”
mentioning
confidence: 99%
“…Early nurse/rehabilitation assessment -This combined indicator of early assessment by a nurse (24) and early assessment of rehabilitation needs (28).…”
mentioning
confidence: 99%